Lymphatic Endothelial Cell Activation and Dendritic Cell Transmigration Is Modified by Genetic Deletion of Clever-1 - Tadayon, Sina; Dunkel, Johannes; Takeda, Akira; Eichin, Dominik; Virtakoivu, Reetta; Elima, Kati; Jalkanen, Sirpa; Hollmén, Maija (Frontiers in Immunology, 2021)
Clever-1 also known as Stabilin-1 and FEEL-1 is a scavenger molecule expressed on a subpopulation of anti-inflammatory macrophages and lymphatic endothelial cells (LECs). However, its role in regulating dendritic cell (DC) trafficking and subsequent effects on immunity have remained unexplored. Using several different approaches we demonstrate that DC trafficking from the skin into the draining lymph nodes is compromised in absence of Clever-1. By adoptive transfer approaches and photoconverting dermal KikGR-expressing DCs we further show that the poor trafficking is due to the impaired entrance into afferent lymphatics. Despite this, ovalbumin injections to the footpads induced a normal proliferative response of OTII T cells in the draining lymph nodes. This could be explained by the increased MHCII expression on DCs and less tolerogenic phenotype of the LN LECs in Clever-1 knockout mice revealed by RNA sequencing. Thus, although less DCs reach the nodes, they are more active in creating antigen specific immune responses suggesting that the DCs migrating within Clever-1 positive lymphatics to the draining lymph node experience immunosuppressive interactions with LECs. In conclusion, besides being a trafficking molecule on lymphatic vasculature Clever-1 is immunosuppressive towards migrating DCs and thus, regulates the magnitude of immune responses created by incoming DCs in the draining lymph nodes.